KAJIAN TUNJANGAN TRANSPORTASI ANGGOTA DPRD KABUPATEN KOTABARU - Oktavianoor, M Rezki; Faozi, Ibnu (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
Additional allowances for Kotabaru Regency DPRD Members, namely Transportation Allowances, since the issuance of Government Regulation Number 18 Year 2017 cannot yet be done. The Kotabaru Regency Government has not been able to determine the value of these benefits. The number of rules relating to the use of state money, makes local governments to be more careful before setting it in the Regents Regents. With so many considerations that need to be considered, a study is needed to legitimize the amount of Transportation Allowance for Members of the Kotabaru Regency DPRD The purpose of this study was to determine the highest value of Transportation Allowances for Kotabaru Regency DPRD Members. The method used is descriptive qualitative, because it needs an in-depth understanding of the rules that limit the object of research. From this study it was found that the highest value for Transportation Allowances was Rp. 16,000,000, and an alternative was also found, Rp. 14,030,000, and a low alternative Rp. 11,750,000. It is recommended that the Kotabaru District Government choose the Alternative Medium as a benefit value.